FEATURES OF THE ASPECTUALLY-TEMPORAL POTENTIAL OF THE OSSETIAN VERBS OF PRESENT TENSE IN COMPARISON WITH THEIR ASPECT-TEMPORARY RUSSIAN EQUIVALENTS (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-2-81-94The meanings of typicality, ordinaryness of action appear in the Ossetian verbs of the present tense as a combination of the potentials of the present irrelevant and imperfect form, and in Russian they are expressed by the forms of the imperfect form in the past tense too. The expresser of these meanings is the verb with the prefix фæ-, in Russian - the context or determinants of the corresponding semantics. Polytemporality of actions with actional shades of habituality and usality is indicated in the Ossetian grammatical category of multiplicity, and in Russian equivalents – by context, lexically, syntactically. The revealed discrepancies are interesting as a reflection of the universal and specific in the linguistic pictures of the world.Keywords: aspectuality, actionality, habituality, usuality, present, linguistic picture of the world